Multiple mitochondrial genes of some sylvatic Brazilian Triatoma: Non-monophyly of the T. brasiliensis subcomplex and the need for a generic revision in the Triatomini - Gardim, Sueli [UNESP]; Almeida, Carlos E. [UNESP]; Takiya, Daniela M.; Oliveira, Jader [UNESP]; Araujo, Renato F.; Cicarelli, Regina Maria Barretto [UNESP]; Rosa, João Aristeu da [UNESP] (Elsevier B.V., 2014)
Multiple fragments of mitochondrial DNA genes (cytochrome b, cytochrome oxidase I, and 16S rDNA) were used to evaluate the phylogenetic relationships among Triatoma melanocephala, Triatoma tibiamaculata, Triatoma vitticeps, and other members of Triatoma brasiliensis subcomplex under a Bayesian framework and maximum parsimony criterion. With the addition of new sequences of T. tibiamaculata and T. vitticeps, Triatoma juazeirensis, Triatoma melanica and the newly sequenced T. melanocephala, the three first sylvatic species, T. melanocephala, T. tibiamaculata and T. vitticeps, were strongly recovered into a clade separate from the other with the remaining Triatoma species from South America, such as the members of T. brasiliensis subcomplex. Panstrongylus megistus was recovered as a sister to T. tibiamaculata, whereas T. vitticeps was a sister to T. melanocephala. This study revealed the non-monophyly of the T. brasiliensis subcomplex, and the polyphyly of Triatoma was reinforced by the placement of these three sylvatic species with Dipetalogaster, Meccus, Mepraia, and Panstrongylus. The results herein shown highlight the need of generic revision in Triatomini. (C) 2014 The Authors. Published by Elsevier B.V.
Keywords: Chagas disease; Phylogeny; Taxonomic revision; Triatominae